TECHNOLOGICAL ADVANCES IN ROSACEA TREATMENT - A COMPREHENSIVE REVIEW - Karolina Ganczar; Michał Mazurek; Marianna Rudzińska; Mikołaj Zalewski; Stanisław Jurkowski; Konrad Zieliński; Łukasz Krzystek; Jagoda Józefczyk; Karolina Buć; Paweł Buć (International Journal of Innovative Technologies in Social Science, 2025)
Rosacea is a chronic inflammatory dermatosis characterized by recurrent facial erythema, flushing, telangiectasia, papules, pustules and in some individuals, phymatous or ocular involvement. Its global prevalence is estimated at approximately 1-3%, with substantial geographic variability and increasing recognition in individuals with skin of color. Although its precise etiology remains multifactorial, contemporary research highlights a complex interplay of neurovascular dysregulation, innate and adaptive immune activation, microbial factors, genetic predisposition, and environmental triggers. Dysregulated cathelicidin expression, kallikrein-5 activity, inflammasome activation, and TRP-channel-mediated neurovascular responses represent key mechanistic pathways. Clinically, rosacea presents with heterogeneous phenotypes encompassing persistent erythema, episodic flushing, inflammatory lesions, phymatous changes, and ocular manifestations, necessitating individualized diagnostic and therapeutic strategies. Evidence-based management integrates phenotype-directed treatment algorithms and data from randomized controlled trials, demonstrating efficacy of topical azelaic acid, ivermectin, and brimonidine, as well as systemic agents such as doxycycline. Recent advances include the introduction of novel topical and systemic therapies, targeted immunomodulators, and combination regimens that address multiple pathogenic pathways. Novel therapies - such as α-adrenergic agonists, topical minocycline formulations, enhanced-delivery topical agents and laser-based technologies - represent promising advancements for phenotype-directed and mechanism-targeted treatment. This review synthesizes current evidence on epidemiology, pathogenesis, clinical features, diagnostic considerations, and contemporary treatment strategies for rosacea, integrating findings from consensus guidelines, clinical trials, and recent translational research.